Holocene Inset Fills of the Odra River in the Racibórz Basin - Wójcicki, Krzysztof; Śleszyński, Przemysław; Mazur, Sławomir (Quaestiones Geographicae, 2010)
Geomorphic and lithological research conducted in the Odra River valley between Koźle and Krapkowice led to recognition of the postglacial development of the upper Odra River valley floor, for the first time, on the basis of a larger number of absolute datings. The formation of the inset alluvial fills by a meandering river started during the Early Holocene at the latest; however, the absence of a clearly developed system of large Late Vistulian palaeomeanders is notable within the analysed reach of the valley. Mid- and Late Holocene alluvial series were deposited by a river that exhibited a tendency to decrease in channel sizes. Nevertheless, large meanders were formed again in historical times. Oxbow fills in the Odra River valley are dominated by mineralogenic deposits. Their sedimentation can be correlated with the accretion of overbank and colluvial sheets in the valley floor. In the light of radiocarbon chronology, a relationship between Neolithic and subsequent phases of settlement in the catchment and the intensive deposition of these sediments cannot be ruled out.